Analisa Tingkat Kebisingan di Area Kerja PLTD Rema Kabupaten Gayo Lues - Anas, Adian Aristia; Zakaria; Darnas, Yeggi; Humaira , Nurhadia (Al-Ard: Jurnal Teknik Lingkungan, 2024)
Noise pollution is a major concern in companies. The utilization of machines to support a production activity in factories or indutries can cause unwanted noise. PLTD Rema is one of diesel power plant companies in Gayo Lues regency which has been running for 18 years. Diesel engines at PLTD Rema will certainly cause noise that disrupt the workers’ hearing. The aims of this study are to identify the noise level, map noise, and examine workers' insights of noise in the area of PLTD Rema. This study shows that the highest noise level of 91.3 dBA lies at sampling point 1. Meanwhile, the lowest value of noise level of 68 dBA lies at sampling point 12. If all of the results of the noise level evaluation at 12 sampling points are evaluated with the Regulation of the Minister of Manpower and Transmigration No. 13 of 2011, the noise levels acquired are unthreatening for all PLTD Rema’s empolyees, except for the area of diesel engines. Moreover, the mapping of noise levels using urfer 13 software consists of 5 different colours (green, blue, red, yellow, and orange). The last one, the workers' perception towards noise has been accepted or H0. Therefore, the noise produced at PLTD Rema has no impact to thier workers’ performance.